2011
DOI: 10.1073/pnas.1101747108
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-rich intestinal protein 2 ( CRIP2 ) acts as a repressor of NF-κB–mediated proangiogenic cytokine transcription to suppress tumorigenesis and angiogenesis

Abstract: Chromosome 14 was transferred into tumorigenic nasopharyngeal carcinoma and esophageal carcinoma cell lines by a microcellmediated chromosome transfer approach. Functional complementation of defects present in the cancer cells suppressed tumor formation. A candidate tumor-suppressor gene, cysteine-rich intestinal protein 2 (CRIP2), located in the hot spot for chromosomal loss at 14q32.3, was identified as an important candidate gene capable of functionally suppressing tumor formation. Previous studies have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 32 publications
1
67
1
Order By: Relevance
“…The cell proliferation assay, cell migration assay, cell adhesion assay and tube formation assay are mature methods to imitate the angiogenesis process in vitro . The in vivo Matrigel plug assay is a mature method to imitate the angiogenesis process in vivo [20,21,22]. Our data showed that AXIIR siRNA was able to inhibit HUVECs proliferation, migration, adhesion, tube formation in vitro and inhibit angiogenesis in vivo (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…The cell proliferation assay, cell migration assay, cell adhesion assay and tube formation assay are mature methods to imitate the angiogenesis process in vitro . The in vivo Matrigel plug assay is a mature method to imitate the angiogenesis process in vivo [20,21,22]. Our data showed that AXIIR siRNA was able to inhibit HUVECs proliferation, migration, adhesion, tube formation in vitro and inhibit angiogenesis in vivo (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Since ALV-J emerged in the 1980s, it has become highly prevalent and caused serious problems in chickens (13). While the western world was successful in eradicating ALV-J from breeding flocks, the virus has gained a stronger foothold in China since 2008 (48).…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is necessary for tumor progression and is driven by molecular interactions between tumor cells and neighboring vascular endothelial cells (13,30). The The between-group differences were analyzed with a two-tailed unpaired t test.…”
Section: Figmentioning
confidence: 99%
“…The immunofluorescence and immunohistochemical (IHC) staining was conducted as previously described (27,28). Antibodies specific for phosphorylated-Histone H3 and g-tubulin were used for IHC and immunofluorescence staining, respectively ( Table 1).…”
Section: Immunofluorescence and Immunohistochemical Stainingmentioning
confidence: 99%